2019
DOI: 10.24931/2413-9432-2018-7-4-16-22
|View full text |Cite
|
Sign up to set email alerts
|

Study of pharmacokinetics of liposomal photosensitiser based on hydroxyaluminium tetra-3-phenylthiophthalocyanine on mice

Abstract: The present work is devoted to the study of pharmacokinetics of infrared photosensitizer (PS) based on hydroxyaluminium tetra‑3‑phenylthiophthalocyanine in a sterically stabilized liposomal form. The study was carried out on adult female mice. The PS was administered once intravenously at a dose of 6 mg / kg. Evaluation of the PS accumulation dynamics in the mice tissues and organs was performed at time intervals from 5 minutes to 7 days using spectral‑fluorescent method. The maximum accumulation of the PS phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Before use, the contents of the vial are rehydrated with water for injection to obtain the recommended concentration 0.25 mg/ ml [3,4].…”
Section: Study Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, the contents of the vial are rehydrated with water for injection to obtain the recommended concentration 0.25 mg/ ml [3,4].…”
Section: Study Medicationmentioning
confidence: 99%
“…In preclinical studies, it was found that Lipophtalocyan has a fairly high selectivity of accumulation in the tumor in relation to normal tissue due to encapsulation of PS in PEG liposomes. The advantages of this drug are high selectivity of exposure to tumor foci, low systemic toxicity, and high efficiency shown in vivo studies [3,4].…”
Section: Introductionmentioning
confidence: 99%